Management and effects of residual limbus inversion following closed reduction in developmental hip dysplasia: Protocol for a multicenter randomized controlled trial - Chenyang Li; Weizheng Zhou; Yufan Chen; Federico Canavese; Lianyong Li (Frontiers Media S.A., 2023)
Closed reduction is a common treatment method for developmental dysplasia of the hip (DDH) in children aged 6-18 months. Residual acetabular dysplasia (RAD) is the most common complication associated with closed reduction. Residual limbus inversion (RLI) is a common condition following DDH closed reduction. Previously, we confirmed that when limbus inversion exceeds 32.2% of the acetabular depth after closed reduction, RLI persists and leads to RAD; however, this was based on a small cohort with a short-term follow-up period. The long-term fate of RLI and the correlation between RLI and RAD have yet to be verified. Therefore, this multicenter clinical study protocol was designed in three parts to investigate the effect of RLI on acetabular development after closed reduction of DDH (a multicenter retrospective cohort study), effect of RLI clearance on acetabular development (a multicenter retrospective and prospective randomized controlled study), and influence of inverted limbus clearance on acetabular development during DDH reduction (a multicenter prospective cohort study). Statistical analysis was performed by assessing the basic measures of acetabular development including the acetabular index and central-edge angle using frontal pelvic radiographs; the magnitude of limbus inversion, cartilaginous acetabular index, and T1ρ mapping values were measured using magnetic resonance imaging. The multicenter retrospective cohort studies required 5 years of follow-up period at minimum, and the prospective randomized controlled studies required reviews of frontal pelvic radiographs every 6 months as well as data pooling every 2 years to compare the short- and mid-term outcomes of hip joint morphological development between the two groups of pediatric patients. This research program is expected to verify that RLI following closed reduction of DDH can affect acetabular development and that limbus excision during DDH reduction can improve postoperative RAD. Therefore, the indication and timing of surgical intervention for RLI after closed reduction of DDH provide a basis for revising the acceptable criteria for utilizing closed reduction of DDH to reduce the incidence of osteoarthritis caused by RAD following DDH treatment.Clinical Trial:http://www.chictr.org.cn/showproj.aspx?proj=35045 (ChiCTR1900020996)